LEGAL PROTECTION AGAINST INDONESIAN WORKERS (TKI) IN ABROAD - Yaya Kareng; Sri Yulianingsih (UNISSULA, 2019)
Protection of migrant workers is all the effort the protection of the interests of prospective workers / migrant workers in realizing the fulfillment of their rights in accordance with the legislation, both before, during, and after work. Protection of migrant workers organized in the International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families (International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families) 1990. In addition there are other international conventions. While the protection of migrant workers is regulated in Act No. 39/2004 on the Placement and Protection of Indonesian Workers Abroad, but this law is more concerned with procedural and procedures for the placement of workers abroad, and only slightly regulate the rights and guarantees the protection of the rights of migrant workers and members of their families. Besides the protection of migrant workers by the government based on the country's constitution, as done by the Department of Foreign Affairs (MOFA) RI. Keywords: Foreign Affairs;